Análise do rumo profissional do trabalhador em relação a sua área de formação - Tavares, Celso Icaro Grijó Costa (2006)
This study has the objective to verify the behavior of Brazilian workers residents in the state of Rio de Janeiro, throughout theirs labor life, concerning their ability to remain - and specialize - in the same professional area originally chosen in its superior educational graduation. As the proposed theme stands beyond the available bibliography, the author needed to analyze the Governmental Labor Ministry Statistical Databases, which provides Brazilian Formal Employment and Unemployment Information. The study started with the selection of three groups of professional occupations from the year of 1994 until the end of 2002. All the professionals who were employed in 1994 had had its trajectory traced up to 2002, as well as were analyzed the ingression behavior at the formal labor market in the year of 1994. Thus, the study encompasses not only the existing employment but also the new job posts created in 1994. For the trajectory tracing, a group of graduated students was selected in some universities of the state of Rio de Janeiro in the year of 1994. The study has clearly shown the impact that the availability of jobs in the same area of the graduation has over the workers decision to remain or change the original career. Such information and conclusions can be a valuable instrument to help students and professionals to plan and decide theirs futures careers, for the planning of public politics of educational investments, as well as for the Brazilian educational institutions to adjust the offering of its courses according to the labor market capacity.